2023
DOI: 10.3390/ijms24076225
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Limosilactobacillus fermentum ME-3 against the Increase in Paracellular Permeability Induced by Chemotherapy or Inflammatory Conditions in Caco-2 Cell Models

Abstract: Chemotherapy- or inflammation-induced increase in intestinal permeability represents a severe element in disease evolution in patients suffering from colorectal cancer and gut inflammatory conditions. Emerging data strongly support the gut microbiota’s role in preserving intestinal barrier integrity, whilst both chemotherapy and gut inflammation alter microbiota composition. Some probiotics might have a strong re-balancing effect on the gut microbiota, also positively affecting intestinal barrier integrity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In this study, by using rat small intestinal epithelial IEC-6 cells, we showed for the first time that HK L-137 decreases permeability by activating the ERK pathway and increases www.nature.com/scientificreports/ expression of TJ genes and proteins. Because effective treatments for increased intestinal permeability have not been established, these results provide new strategies for the prevention and treatment of leaky gut 14 . An intact intestinal barrier is known to be important in the prevention of disease and maintenance of health 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, by using rat small intestinal epithelial IEC-6 cells, we showed for the first time that HK L-137 decreases permeability by activating the ERK pathway and increases www.nature.com/scientificreports/ expression of TJ genes and proteins. Because effective treatments for increased intestinal permeability have not been established, these results provide new strategies for the prevention and treatment of leaky gut 14 . An intact intestinal barrier is known to be important in the prevention of disease and maintenance of health 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many people are constantly exposed to factors that induce leaky gut in their daily lives. However, currently no established treatment is available for the condition, so early treatment and prevention methods are urgently needed 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The GIT of ruminants is challenged with different stressors, including potentially harmful bacteria, mycotoxins, reactive oxygen species ( ROS ), endotoxins, and pro-inflammatory cytokines that may lead to the occurrence of the hyperpermeable intestine syndrome ( Copani et al., 2021 ; Boll et al., 2024 ; de Gregorio et al., 2023 ). This syndrome, also known as leaky gut, alters the GIT microbiota ( O’Hara, et al., 2020 ), triggering an inflammatory response that leads to production losses in beef and dairy cattle ( Cooke, 2017 ; Kvidera et al., 2017a , b ; Briggs et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%